PROSES HUKUM PEMBUKTIAN TERBALIK TERBATAS DALAM PERKARA PIDANA KORUPSI - Saiful. L (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACTBy lifting the title essay "UPSIDE OF EVIDENCE LITIGATION CRIMINAL CASE LIMITED TO CORRUPTION".to know how the process of proving the limited upside in the case of Corruption, as well as what obstacles are faced by law enforcement officials, especially against the investigators in the case-handling corruption cases.To be able to enforce the law in terms of return loss of the State, then the law of proof is the main key in order to facilitate the state in back losses due to acts of corruption committed by the perpetrator of Corruption.Legal Process Reversed Limited Evidence In Criminal Case of Corruption, is a defendant HKL if he wanted to prove that he really is innocent, and it is already regulated in Law No. 31 Year 1999 jo 20 of 2001 on Corruption EradicationConditions Inverted proof has been provided in Article 28 of Law 31 of 1999 on Corruption Eradication, and it can be done either by the investigators in this case as Prosecution Attorney General and the defendant as the party that is alleged to have committed an act that meet the elements of corruption offense.Implementation of the provisions of article 28 of Law No.31 of 1999 concerning Limited Upside Evidence in Criminal Corruption can only be done when each party really wants to prove the real truth and really want to uphold justice for the sake of maintaining law and it can be realized if there is intention and awareness of the parties in the interest of the State.But the fact the handling of criminal cases of corruption investigator State is considered not seriously combat corruption to restore the loss of the State, it can be measured from several decisions criminal cases of corruption by Judge Corruption, often deciding the case by simply imprison the perpetrator alone while foreclosure treasure wealth defendant did not seizure due to non-realization of article 28 of Law 31 of 1999 was related data collection assets of the defendant in order to restore a loss of State.Keywords: Evidence Reversed reinforced through Article 28 UU.No 31/1999 On Eradication of Korupsin 1999 to the real truth in the case of corruption.